Wyclif and the wheel of time - Wilks, Michael (Studies in church history, 1997)
During the 1370s Wyclif wrote to defend a monarchy which made extensive use of bishops and other clergy in the royal administration and yet was faced with aristocratic factions encouraged by bishops like Wykeham and Courtenay who espoused papal supremacy, if not out of conviction, at least as a very convenient weapon to support their independence against royal absolutism. At first sight Wyclifs attempts to define the right relationship between royal and episcopal, temporal and spiritual, power seem as confused as the contemporary political situation. His works contain such a wide range of theories from orthodox two swords dualism to a radical rejection of ecclesiastical authority well beyond that of Marsilius and Ockham that it seems as if his only interest was in collecting every anti-hierocratic idea available for use against the papacy. The purpose of this paper is to suggest that a much more coherent view of episcopal power can be detected beneath his tirades if it is appreciated that his continual demand for a great reform, a reformatio regni et ecclesiae, is inseparably linked to his understanding of the history of the Christian Church, and that in this way Wyclif anticipates Montesquieu in requiring a time factor as a necessary ingredient in constitutional arrangements.